The features of Chlamydomonas applanata (Chlorophyta, Polytominia) in unmotile stage (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The five strains of Chlamydomonas applanata in immotile stage in a culture on agar medium were investigated. The main morphological features of Ch. applanata which distinguished this species from other species of genus Сhlamydomonas s.l. were established. The main features are: a) the absence of central triplet cell wall multiplication; b) the presence of colonial mucilage sporangium origin; c) continuous starch sheath of pyrenoid; d) the presence of red spherical akinetos-like cells and spherical green zygotes with thickened smooth wall; e) the presence of rudimentary flagella in zoospores in sporangia.
Keywords: algae, Chlorophyta, Polytominia, Chlamydomonas, morphology, taxonomy, identification.